Shielding polarizabilities via continuous transformation of the origin of the current density in the set of small molecules: H2O2, F2, H2C2, H2CO, NH3, HCN, and HNC - Caputo, M.C. (2000)
A procedure, based on a continuous transformation of the origin of the (quantum mechanical) current density that sets the diamagnetic contribution to zero (CTOCD-DZ) all over the molecular domain, is applied to determine shielding polarizabilities to first order in a perturbing electric field. In any calculations relying on the algebraic approximation, irrespective of size and quality of the (gaugeless) basis set employed, all the components of the CTOCD-DZ magnetic shielding polarizability are origin independent, and the constraints for charge and current conservation are exactly satisfied. The effects of a static uniform electric field on the nuclear magnetic resonance (NMR) shielding of H2O2, F2, H2C2, H2CO, NH3, HCN, and HNC molecules have been investigated within the CTOCD-DZ method, and compared with the conventional results evaluated via the same basis sets, and with theoretical results taken from the literature. © 2000 American Institute of Physics.